Exploratory Factor Analysis of the Strength of the Cultural Affiliation Scale. Issue 1 (January 2017) - Kruse, Julie A.; Williams, Reg A.; Mood, Darlene
Abstract : Background: Within the United States, there are individuals who retain the traditions and beliefs of cultural groups that vary from the general majority population. Both healthcare providers and researchers have reported that many individuals who live in but are less affiliated with the dominant culture tend to have less positive health outcomes. Objective: The purpose of this study is to use factor analysis to assess the psychometric properties of Mood's 18-item Strength of Cultural Affiliation Scale (SCAS). Methods: The SCAS was administered to 604 participants from a randomized clinical trial of cancer patients who were treated with radiotherapy at a large central city hospital located in the Midwest. Results: Confirmatory Factor Analyses using Principal Component Analysis with Oblimin Rotation indicated a 16-item, 4-factor final solution with the following subscales: factor 1, lifestyle (7 items); factor 2, language and cultural-specific holidays (3 items); factor 3, relationships (4 items); and factor 4, cultural health practices (2 items). Conclusion: The SCAS demonstrated high reliability and content, construct, discriminant, convergent, divergent, and predictive validity. Implications for Practice: The SCAS seems to be a reliable and valid tool for practitioners to use to assess a patient's strength of cultural affiliation to provide the best culturally sensitive care possible for the patient.